Non-ambulatory Duchenne muscular dystrophy: observations, interventions, and outcomes on a single case - Sevria Yetty Anggraina Noer; Sunartini Sunartini; Purnomo Suryantoro (Indonesian Pediatric Society, 2022)
Duchenne muscular dystrophy (DMD) is a X-linked recessive gene defect manifesting as a fatal, progressive neuromuscular disease. Treatment goals aim to inhibit disease progression, increase patients’ quality of life, and lengthen life expectancy. We report here a single case of non-ambulatory DMD.